Union decline in Britain - David G. Blanchflower; Alex Bryson (Institute for the Study of Labor (IZA), 2008)
This paper investigates the demise of unionisation in British private sector workplaces over the last quarter century. We show that dramatic union decline has occurred across all types of workplace. Although the union wage premium persists it is quite small in 2004. Negative union effects on employment growth and financial performance are largely confined to the 1980s. Managerial perceptions of the climate of relations between managers and workers have deteriorated since the early 1980s across the whole private sector, whether the workplace is unionised or not.
urn:nbn:de:101:1-2008041401
Keywords: J51; 330; Trade unions; wages; employment growth; financial performance; Arbeitsbeziehungen; Gewerkschaftsbewegung; Gewerkschaftlicher Organisationsgrad; Arbeitskonflikt; Arbeitslosigkeit; Lohnverhandlungen; Großbritannien